Creating visually effective materials for English learners - Kleckova, Gabriela (TESOL PRESS, 2019)
"This ebook is designed to help meet the needs of TESOL professionals in the areas of visual literacy and communication inside and outside ESOL classrooms. It includes practical ideas for writers and teachers and shows how TESOL practitioners can make their own materials more accessible and appealing to their learners and other audiences."--TESOL Press bookstore viewed April 13, 2022.